Engineering Performance Of High Strength Concrete Containing Steel Fibre Reinforcement - Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2013)
The development and utilization of the high strength concrete in the construction industry have been increasing rapidly. Fiber reinforced concrete is introduced to overcome the weakness of the conventional concrete because concrete normally can crack under a low tensile force and it is known to be brittle. Steel fibre is proved to be the popular and best combination in the high strength concrete to result the best in the mechanical and durability properties of high strength concrete with consideration of curing time, steel fibre geometry, concrete grade and else more. The incorporation of steel fibre in the mortar mixture is known as steel fibre reinforced concrete have the potential to produce improvement in the workability, strength, ductility and the deformation of high strength concrete. Besides that, steel fibre also increases the tensile strength of concrete and improves the mechanical properties of the steel fibre reinforced concrete. The range for any high strength concrete is between 60MPa-100MPa. Steel fibre reinforced concrete which contains straight fibres has poorer physical properties than that containing hooked end stainless steel fibre due to the length and the hooked steel fibre provide a better effective aspects ratio. Normally, steel fibre tensile strength is in the range of 1100MPa-1700MPa. Addition of less steel fibre volumes in the range of 0.5% to 1.0% can produce better increase in the flexural fatigue strength. The strength can be increased with addition of steel fibre up to certain percentage. This paper will review and present some basic properties of steel fibre reinforced concrete such as mechanical, workability and durability properties.